PROTOTYPE PENDETEKSI TSUNAMI DI DAERAH PESISIR PANTAI BERBASIS RADIO FREQUENCY SEBAGAI PERINGATAN TSUNAMI DINI - Wartiyati Wartiyati; Ilham Gumanti; Putri Ramdhany; Toto Supriyanto (Politeknik Negeri Jakarta, 2015)
Abstract This prototype is use to provide the information to people around the coast when the tsunami will occur. This prototype was made because there are many tsunami prone areas in Indonesia, especially the west coast of Sumatra. Until now, people still don’t understand the characteristics of tsunami and lack of tsunami early detection. This prototype works by utilizing the characteristics of the tsunami, the drastic decline of sea water. The prototype consists of two parts, the transmitter located at sea (tsunami detection) and receiver located on land (observation post). The detectior is made of buoys connected to the lever using a rope. When the appliance detects a tsunami, the lever will hit the switch and float drawn down to touch the sea floor, the process indicates the tide as a sign of tsunami will come. The transmitter sends a signal 108,7MHz using FM radio with FSK modulation. At the receiver, the analog signal is processed by the FM receiver and it become the data of tsunami detection with a frequency of 1217Hz. This signal is then converted into a digital signal using FSK demodulator then into the microcontroller as an input. Microcontroller process the data and activates an alarm buzzer as early tsunami warning and sending SMS notification